Case report, citizen science reveals the occurrence of Botflies (Diptera: Oestridae) in the Czech Republic and Slovakia - Oboňa, Jozef; Adamcová, Marcela; Mlynárová, Laura; Mokránová, Veronika; Sychra, Oldřich (Annals of parasitology, 2024)
We present a case of a botfly larva (Gasterophilus intestinalis (De Geer, 1776)) that was removed from a horse's stomach during gastroscopy. Additionally, we provide a detailed yet unconventional perspective on the research of botfly presence in the Czech Republic and Slovakia. Through citizen science, we confirm the occurrence of two species of Hypodermatinae, among which Hypoderma diana Brauer, 1858 is relatively common. In the subfamily Oestrinae, we confirmed the occurrence of three species. Cephenemyia stimulator (Clark, 1815) is very common, which suggests that this species could negatively impact deer populations and their vitality. On the other hand, species reproductively linked to livestock (cattle, sheep, and goats) are relatively rare, which may be associated with the transition to stable-based farming of these animals.
Keywords: občanská věda; Animals; Horses; Česká republika; Myiasis; Slovakia; Citizen Science; Slovenská republika; Diptera; Larva; zvířata; Czech Republic; myiáza; larva; koně